2020
DOI: 10.1111/apt.15750
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: medical therapy for fibrostenosing Crohn’s disease

Abstract: Background: Medical therapy and/or endoscopic balloon dilation with intralesional therapies are options for the treatment of small bowel fibrostenotic Crohn's disease (CD). Aim: To perform a systematic review summarising evidence for efficacy of systemic and endoscopic intralesional medical therapy in established small bowel strictures in adult CD patients. Methods: A systematic search of MEDLINE, EMBASE, CENTRAL and Scopus was conducted. Primary outcomes were rates of surgical resection and repeat endoscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 61 publications
(169 reference statements)
2
34
0
1
Order By: Relevance
“…This may in part be explained by the reported anti-MAP activity of cytostatic agents, but this has not previously been reported in cases of stricturing CD[ 29 , 30 ]. Notably this correlation was not found with biologic therapy, which has been described to decrease both the immunogenicity and intracellular survival of MAP, and alleviate strictures[ 10 - 12 , 31 ]. In our study, patient demographics, area of involvement, number of strictures, duration of treatment and clinical response were not significantly related to stricture outcome.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This may in part be explained by the reported anti-MAP activity of cytostatic agents, but this has not previously been reported in cases of stricturing CD[ 29 , 30 ]. Notably this correlation was not found with biologic therapy, which has been described to decrease both the immunogenicity and intracellular survival of MAP, and alleviate strictures[ 10 - 12 , 31 ]. In our study, patient demographics, area of involvement, number of strictures, duration of treatment and clinical response were not significantly related to stricture outcome.…”
Section: Discussionmentioning
confidence: 98%
“…In our review, AMAT provided a high rate of stricture resolution (67%) compared with other therapies in the limited available literature. Recently, the Stricture Therapy and Research Consortium identified only ten studies involving stricture therapy, none of which included antibiotic therapy, and concede there is a need for RCTs into systemic medical therapies for CD strictures[ 10 ]. To date, the largest multicenter, prospective study (CREOLE), found adalimumab displayed efficacy in stricture success in 62/97 (64%) patients[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent management is dependent on strictures' inflammation degree and morphometrics, such as location and length, assessed by biomarkers (e.g., C-reactive protein, erythrocyte sedimentation rate, and fecal calprotectin), endoscopy, computed tomography, or magnetic resonance imaging. Current complications (such as phlegmon, abscess, dysplasia, or malignancy) and patient preferences should also be taken into account [5,54].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Moran et al [42] evaluated factors associated with failure of medical therapy: patients with stricturing or penetrating disease phenotypes had >6-and 3-fold increased risks of failing medical therapy and requiring surgical intervention. Indeed, very little evidence supports the use of biologic agents for resolving internal penetrating disease or for "cold" fibrostenotic strictures [43,44]. In these scenarios, as previously stated, delaying inevitable surgery by introducing a biologic agent may have detrimental consequences as it changes the benefit-risk proposition.…”
Section: Early Surgery Versus Early Medical Therapy: An Individualized Choicementioning
confidence: 99%